Volume 4B: Materials and Fabrication 2022
DOI: 10.1115/pvp2022-84902
|View full text |Cite
|
Sign up to set email alerts
|

New Strength Theory and Its Application to Determine Burst Pressure of Thick-Wall Pressure Vessels

Abstract: The classical Tresca and von Mises strength theories have been utilized extensively for pressure vessel and pipeline design. For pressure vessel design, ASME B&PV code was developed using both Tresca and von Mises strength theories, where the yield strength (YS) was used for an elastic design and the ultimate tensile strength (UTS) was used for an elastic-plastic design. For pipeline design, ASME B31.3, B31G, or other codes were developed using the Tresca strength theory coupled with the YS or a flow stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The combined database of 229 points was compared to the analytical thick-walled PV burst equation recently derived in reference [8], given as…”
Section: Comparison Of Combined Database With Theoretical Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined database of 229 points was compared to the analytical thick-walled PV burst equation recently derived in reference [8], given as…”
Section: Comparison Of Combined Database With Theoretical Solutionsmentioning
confidence: 99%
“…π‘₯ π‘šπ‘Žπ‘₯ βˆ’ π‘₯ π‘šπ‘–π‘› (8) where π‘₯ Μ‚ is the normalized variable. A scoping study found that ANNs for PV burst performed much better when variable normalization was used, thus it was applied to each variable for all models presented here.…”
Section: π‘₯ Μ‚= π‘₯ βˆ’ π‘₯ π‘šπ‘–π‘›mentioning
confidence: 99%
See 1 more Smart Citation
“…Ihn and Nguyen evaluated these and other formulae against FEA models of pressurized water reactor cooling components and found that their burst strength predictions could vary by as much as 45% [17]. Recently, in reference [18], the Zhu-Leis theory using the average shear stress to predict pressure vessels was extended to thick-walled PV's as well, providing the first analytical theory capable of accurately predicting the burst pressure for both thin and thick-walled PVs.…”
Section: Introductionmentioning
confidence: 99%
“…al. showed that if the mean diameter is used instead of the outside diameter (which is typically used) for thin and thick-walled PVs, the Zhu-Leis thick-walled theory predicts the burst pressure with similar accuracy to the thin-walled theory [18]. This is explored herein using python code to generate a database of FEA derived PV burst predictions for different geometries and materials.…”
Section: Introductionmentioning
confidence: 99%